Narrative of Religion: The Experiences of Muslim Worship on the Umrah Pilgrimage - Fernando, Henky; Larasati, Yuniar Galuh; Qudsy, Saifuddin Zuhri; Santoso, Try Riduwan (Universitas Gadjah Mada, 2024)
Narratives of Muslim experiences have simultaneously influenced the knowledge and meaningon the umrah pilgrimage to become increasingly complex and contextual. The narrative of the experiences of Muslim worship on the umrah pilgrimage has not been given much scientific attention in previous studies. This study focuses on the question “What is the narrative of the experience of Muslim worship on the umrah pilgrimage?” To answer this question, this study uses a qualitative descriptive approach in exploring the knowledge, meaning, and experiences of Muslim worship on the umrah pilgrimage which is disseminated online news. The process of collecting and reading the news is focused on news headlines that contain stories and events experienced by Muslims while performing the Umrah pilgrimage. Findings in this study show that the narratives of Muslim worship experience when carrying out the umrah pilgrimage are not least influenced by spiritual and cultural values that are evaluative and reflective in nature. Based on these findings it is possible to formulate a concept of Narrative of religion as a novelty in this study. This study also recommends the importance of comparing the experiences of Muslim in carrying out the umrah and Hajj pilgrimages, in order to comprehensive and more empirical understanding.